Universities and Scholars in East Africa - (:unkn) unknown (My University, 2012)
All books have a history and this one is no exception. It is both simple and exemplary. The research program “Academicians and Universities in East Africa, New Functions and Remits, Compared Experiences Approach, Collective and Institutional Strategies” , that informs this publication, arose from the observation that academicians and universities resisted all forms of de-structuring that affected countries in East Africa and the Great Lakes Region after a decade of political, ethnic, social and economic upheavals. A good example is the symbolic history of Makerere University as well as the observation that universities have since the turn of the century been undergoing expansion if not renaissance. However, this double reality, which is sometimes successive and sometimes combined, raises in the daily life of academicians a number of problems, issues and challenges. teaching and research professors drawn from major East African Universities and African experts specialised in the region, who have, at one moment or another of their career, worked in these Universities. Beyond the initial general problem, these studies, which are also testimonies, concern unique national situations and contexts in Burundi, Kenya, Uganda, Rwanda, the Democratic Republic of Congo and Tanzania dealing with problems shared by academicians in the five countries of the East African Community, in the Great Lakes Region and, more specifically, the future of Humanities and Social Sciences, Universities, faculties, departments and research centres concerned with this discipline.
Keywords: African Research